Evaluasi Akuntabilitas dan Efektivitas Pengelolaan Dana Desa di Kabupaten Bangka dan Kabupaten Belitung: Suatu Kajian Komprehensif - Anggraeni Yunita; Christianingrum Christianingrum (UNSIKA (Universitas Singaperbangsa Karawang), 2019)
Under Law no. 6 Year 2014 on Village, the government's goal of forming Village Fund is because the government wants to improve the welfare of rural communities; improving the quality of life of villagers; tackling poverty; as well as creating economic growth with more revenue sharing. In relation to the management of the village funds, the Corruption Eradication Commission (KPK), based on the results of the study conducted in 2014, found 14 potential problems for village fund management related to Village Fund Allocation (ADD) and Village Funds divided into four (4) aspects of regulatory and institutional aspects, aspects of governance, supervisory and human resources aspects. The purpose of this study is to evaluate whether the management of village funds has been accountable and effective in terms of regulatory and institutional aspects, the management of funds, supervision and human resources that will be assessed using a qualitative approach. The conclusions obtained from the preliminary study result, village fund management in 2015 are still not optimal, but for the 2016 village funds management has been well done since the weaknesses in 2015 became inputs for central, district and village governments for village funds management to be more well again.